2018
DOI: 10.2147/opth.s186929
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcome of three different procedures for childhood glaucoma

Abstract: PurposeTo investigate the long-term postoperative outcome of three surgical procedures for childhood glaucoma.Patients and methodsIn this retrospective study, the patients were divided into a goniotomy group, a trabeculotomy group, and a filtering surgery group, based on the initial surgical procedure. Failure was defined as an IOP ≥21 mmHg with medication at two consecutive visits. A Kaplan–Meier analysis was applied to calculate the probability of success. Additional metrics included IOP, number of additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In a study conducted by Huang et al, the success rate of 65.2% for goniotomy after ten years was noted. 18 This difference in success rate may be explained by a more extended follow-up period, up to 10 years. A study conducted in Northern Tanzania showed a success rate of 38% at 12 months follow up.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Huang et al, the success rate of 65.2% for goniotomy after ten years was noted. 18 This difference in success rate may be explained by a more extended follow-up period, up to 10 years. A study conducted in Northern Tanzania showed a success rate of 38% at 12 months follow up.…”
Section: Discussionmentioning
confidence: 99%